THU0533 Pain Intensity and Threshold in Rheumatoid Arthritis, Psoriatic Arthritis and Ankylosing Spondylitis Patients: Correlations with the Hamilton Depression Rating Scale. (23rd January 2014) - Bagnato, G.; Atteritano, M.; Sorbara, S.; De Andres, I.; Talotta, R.; Corallo, G.; Verduci, E.; Miceli, G.; Sangari, D.; Visalli, E.; Marino, N.; Morgante, S.; et al.
Abstract : Background: Individuals suffering from chronic pain are frequently affected by depression, which in turn increases the risk of development of chronic pain complaints over time. Objectives: This study aims to investigate the relationship between depression and pain intensity and threshold in a cohort of rheumatic patients compared to healthy subjects. Methods: 124 individuals of whom 50 affected by rheumatoid arthritis (RA), 23 by psoriatic arthritis (PsA), 23 by ankylosing spondylitis (AS) and 28 age-matched controls without chronic pain underwent quantitative sensory testing (QST) to assess pressure pain threshold with an algometer. Pain intensity was evaluated through the Visual Analogue Scale (VAS) and depression through the Hamilton Depression rating Scale (HAMD). Results: A significant reverse correlation between HAMD values and algometer scores was found in the entire cohort of patients (p<0.0001), in controls (p=0.002) and also in RA (p=0.002), PsA (p<0.0002) and AS (p=0.02) patients when analyzed separately, while no significant correlation was found between HAMD and VAS values or algometer scores and VAS. We found lower pain thresholds in RA and PsA patients while no difference has been evidenced in AS patients compared to healthy controls. HAMD scores were also significantly higher in rheumatic patients than in controls. Conclusions: The evaluation of chronic pain in patients affected by rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis that display comorbid depression seems more reproducible and reliable with the use of an algometer which, therefore, could be considered an useful instrument in pain/depression overlap management. Disclosure of Interest: None Declared